THE ROLE OF PHYSICAL EDUCATION AND SPORTS ON THE BASIS OF INVATIONAL APPROACHES IN STRENGTHENING HUMAN HEALTH - Rahimov, Sh.M.; Xojimurodova, M.K. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
This article is about strengthening the natural health of the members of our society through physical education and sports.
Keywords: Sports; health training; mass sports; educational technologies; training; innovative approach; physical knowledge; physical education; immunity; pedagogical observation; loading; Olympic games